1984
DOI: 10.1002/ajmg.1320190216
|View full text |Cite
|
Sign up to set email alerts
|

Effects of selection for serum cholesterol concentrations on serum lipid concentrations and body weight in baboons

Abstract: We examined the results of one generation of selection for serum cholesterol (SC) concentration on low density lipoprotein cholesterol (LDL-C), high density lipoprotein cholesterol (HDL-C), and triglyceride concentrations and weight in baboons (Papio cynocephalus). Parents of two lines (high SC response and low SC response) were chosen based on their SC response to a 4-month challenge with a cholesterol and saturated fat enriched diet. Parents of the control line were chosen without regard for SC levels. Expre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
11
0

Year Published

1987
1987
2002
2002

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 22 publications
(11 citation statements)
references
References 24 publications
0
11
0
Order By: Relevance
“…Although we cannot rule out this possibility, we have not observed, in density gradient analyses, 13,17,21 apo(a) proteins in density fractions more buoyant than Lp(a). Furthermore, baboons tend to have relatively low plasma triglyceride concentrations (Ϸ52 mg/dL on the basal diet and Ϸ37 mg/dL on the HFHC diet 35 and, consequently, low levels of TRLs.…”
Section: Discussionmentioning
confidence: 99%
“…Although we cannot rule out this possibility, we have not observed, in density gradient analyses, 13,17,21 apo(a) proteins in density fractions more buoyant than Lp(a). Furthermore, baboons tend to have relatively low plasma triglyceride concentrations (Ϸ52 mg/dL on the basal diet and Ϸ37 mg/dL on the HFHC diet 35 and, consequently, low levels of TRLs.…”
Section: Discussionmentioning
confidence: 99%
“…Both the basal and challenge levels of LDL and HDL were highly heritable. 4 Subsequent studies focused on detecting and identifying the responsible genes by molecular [5][6][7][8] and statistical 9 -11 genetic strategies. A previous study suggested that the response to dietary cholesterol and to dietary saturated fat might be controlled by separate genes in baboons.…”
mentioning
confidence: 99%
“…The HDL-C levels of the juvenile baboons, offspring of selectively bred high-and low-responding parents, were observed to diverge from birth through 2 years of age while they were fed identical diets. 30,31 Although affecting HDL-C levels in these baboons, neither an unidentified major locus nor the LCAT structural locus exerted an effect on lipemic response 32,33 ; however, another major locus for apoA1 was found to account for 33% of the variance in apoA1 response to diet. 34 Studies in humans and nonhuman animals alike strongly support the notion that genes influence lipemic response of HDL-C or its subfractions.…”
mentioning
confidence: 79%